Correlation between Muscle Strength, Calf Circumference, Vitamin D, and IGF-1 on Depression in the Elderly - Paskalis Andrew Gunawan; Anastasia Ratnawati Biromo; Alexander Halim Santoso; Bryan Anna Wijaya; Kasvana Kasvana; Louise Audrey Sukianto; Yohanes Firmansyah (Universitas Malahayati, 2026)
ABSTRACT Depression in the elderly is a multifaceted issue influenced by various physiological factors. This study investigates the correlation between muscle strength, calf circumference, Vitamin D, and Insulin-like Growth Factor 1 (IGF-1) levels and their collective impact on depression among the elderly. This study aims to understand the correlation between muscle strength, calf circumference, Vitamin D, and IGF-1 levels on depression to develop targeted interventions to improve mental health outcomes in this demographic. This cross-sectional study involved 82 older people at RPTRA Krendang. Depression is measured using the Geriatric Depression Scale (GDS). Data were analyzed using Spearman's Rho to see the Correlation between Muscle Strength, Calf Circumference, Vitamin D, and IGF-1 on Depression in the Elderly. The study found most respondents were female (78%), with an average age of 74.34 years, and according to the Geriatric Depression Scale, the majority (59.8%) of respondents were normal. This study highlighted significant correlations between muscle strength, calf circumference, and decreased Vitamin D and IGF-1 levels with higher depression scores. These findings suggest that diminished physical health markers and nutrient deficiencies are associated with increased depressive symptoms in the elderly. Measuring muscle strength, calf circumference, Vitamin D, and IGF-1 levels is a good approach to understanding depression in the elderly that will lead to effective interventions by health workers and improve quality of life. Keywords: Calf Circumference; Depression; IGF-1; Muscle Strength; Vitamin D.